2003
DOI: 10.1097/01.asn.0000038687.24289.83
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Associates with Actin and Limits Injury in Energy Depleted Renal Epithelia

Abstract: Abstract. The purpose of the study was to determine whether Hsp27 interacts with actin and could protect against selected manifestations of injury from energy depletion in renal epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 26 publications
5
44
0
2
Order By: Relevance
“…13 Indeed, stress or injury in renal tubule cells promote association or colocalization of HSP27 with F-actin leading to cytoprotection in vitro. 51,52 We propose that renal overexpression of huA 1 ARs led to increased HSP27 synthesis in the injected kidney with resultant F-actin stabilization with subsequent protection against AKI after liver IR.…”
Section: Discussionmentioning
confidence: 96%
“…13 Indeed, stress or injury in renal tubule cells promote association or colocalization of HSP27 with F-actin leading to cytoprotection in vitro. 51,52 We propose that renal overexpression of huA 1 ARs led to increased HSP27 synthesis in the injected kidney with resultant F-actin stabilization with subsequent protection against AKI after liver IR.…”
Section: Discussionmentioning
confidence: 96%
“…Although previous studies have implicated Hsp27 in regulation of actin polymerization, the primary molecular interaction considered was direct binding of Hsp27 to actin subunits (Landry and Huot 1999;Butt et al 2001;Bitar 2002;Van Why et al 2003;Pichon et al 2004;Chaudhuri and Smith 2008) or binding to actin-associated tropomyosin and caldesmon Bitar 2004, 2006). Using purified Hsp27 and actin, in vitro studies have shown that nonphosphorylated Hsp27 inhibits actin polymerization, while phosphorylated Hsp27 permits actin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the cytoprotective effect of HSP induced by heat (8,11,41), injury (3,4,10,12), or transfection (15,18) provides important correlative, but not definitive, evidence of a key role for HSP in modulating acute cellular injury. If increased expression of HSP is protective, then downregulation should augment cellular injury or impair restitution of cellular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies aimed at establishing a causative link between HSP induction and cytoprotection have examined the effects of overexpression of the heat-shock response by means of preconditioning (8 -12), pharmacologic induction (13,14), or transfection (15). Preconditioning requires the application of an initial injury to induce HSP, which confounds the interpretation of outcome.…”
mentioning
confidence: 99%